Vie et survie de la tradition auvergnate - Elizabeth Poe (Revue des Langues Romanes)
Surrounded by a court of troubadours who sing of its merits and fix its representation for posterity, the Dauphin of Auvergne occupies a central place in the diffusion of the Auvergne troubadour tradition, dominated by the Court of Le Puy. The troubadours themselves are located there in a community and continuity, up to the sirventès of the Moine de Montaudon, who testifies to its decline without damaging its image for subsequent centuries, rich in laudatory references until the end of the Middle Ages.